Adaptation of the TIMBRE methodology for brownfields gully erosion analysis in urban areas - Kuhn, Caiubi Emanuel Souza [UNESP]; Reis, Fábio Augusto Gomes Vieira [UNESP]; Santos, Flávia Regina Pereira; Zarfl, Christiane; Grathwohl, Peter; Cabral, Victor [UNESP] (Elsevier, 2024)
Soil erosion is a concern in many parts of the world, causing environmental and social impacts. Aiming at obtaining indicators of the recovery of brownfields created by gullies in urban areas, this study adapts the Tailored Improvement of Brownfield Regeneration in Europe (TIMBRE) for the analysis and classification of areas affected by gullies in the city of Bauru, Brazil. The TIMBRE methodology assists in the decision-making of priority areas for remediation and their reinsertion in urban spaces. The inventory of areas affected by gullies was compiled based on the analysis of two image sets (2004 and 2020) available on Google Earth. For the classification of brownfields, three classes were considered: Class 1 - local potential for business development, Class 2 - attractiveness and marketing, and Class 3 – environmental risks. These results demonstrate a correlation between gullies and urban expansion. The inventory identified 175 gullies in the municipality's urban perimeter in 2004, which affected an area of over 64 ha. In 2020, the number of gullies increased to 189, but the affected area decreased to 62 ha due to the recovery of some large gullies. The proposed methodology identified the area of Quinta da Bela Olinda as the one with the highest scores in all three classifications. Quinta da Bela Olinda is the location that has a local potential for business development, as it is the most attractive brownfield, as well as the area with the highest environmental risk. This area should, thus, be prioritized by public management for remediation. In conclusion, the proposed method of analysis can be transferred to other areas with adaptations in the criteria used and, therefore, may facilitate the management of urban areas affected by gullies in other places around the world.
Keywords: Brownfields regeneration; Greenfields; Gully remediation; Soil degradation